(untitled) - Hall, G.K. (Boston, Mass., 1987)
The pace of technological change is quickening all the time. Hardly a day goes by without some new innovation which promises to revolutionize the way live.
Keywords: Technology,Công nghệ; Encyclopedias,Bách khoa toàn thư